Designing Bakgor Bobo Cen Brand Campaign to Increase Brand Awareness on Instagram - Shannen, Shannen; Tjandrawibawa, Paulina (VCD: Journal of Visual Communication Design, 2023)
To be able to have branding that is able to maintain brand performance in this industry 4.0, the right branding strategy is needed in strengthening branding, one of which is also to increase brand awareness. Branding is something that differentiates a brand from other similar competitors. The purpose of this research journal is to guide the author's literature study review on the right branding strategy that can be executed by the Bakgor Bobo Cen brand, so as to increase brand awareness in the brand's target audience. By using the literature study review method on several national and international journals and books with the theme of tips and strategies in branding. The results showed that designing a brand campaign on Instagram can be a solution for Bakgor Bobo Cen in increasing brand awareness. In this study, the Bakgor Bobo Cen brand will use Instagram as a medium to increase awareness in the target market by utilising relevant features on Instagram with the needs of potential customers. So that if the concept of branding strategy with brand campaigns in this study can be used as direction and guidance by the Bakgor Bobo Cen brand to increase awareness of the Bakgor Bobo Cen target audience.